Agrarian Reform: Human Rights Enforcement and Good Governance - Akib, Israwati; Pide, Suriaman Mustari; Borahima, Anwar; Lahae, Kahar (International Journal of Psychosocial Rehabilitation, 2020)
Cases of human rights violations in Indonesia began to spread in the agrarian sector. Many cases of disputes that develop into agrarian conflicts. This was triggered by differences in the legal basis used for claims for land ownership. One of the characteristics of the phenomenon of agrarian conflict in Indonesia is that the involvement of the state will not be recognized by the control and cultivation of land by the people on lands which are then handed over to other parties This article is normative legal research. The resultshow that Agrarian reform is an effort to strengthen community assets in the form of land, as well as efforts to improve community access to land. Legal systems must be able to encourage and develop development in a balanced manner and protect and promote social justice. Through the concept of human rights will be known aspects of basic human needs that have not been met, so that the arguments and direction of development can be developed. Agrarian reform is expected to be able to change the whole existing order in applying the principles of good governance as one of the tools that can create a sustainable and just governance. These developments increasingly require the government to work better in serving the community in more creative and modern ways, namely through the active participation of the community and the private sector that applies the principles of good governance.